Megaprepuce Reconstruction: A Single Center Experience - Podestá, Miguel Luis; Podestá, Miguel (Frontiers in Pediatrics, 2018)
Introduction Surgical treatment of congenital megaprepuce is challenging and controversial. We report our 10-year experience treating patients with this deformity using a standardized procedure that has similarities to a technique reported by Smeulders et al. (1). Our postoperative complications and mid-term follow-up cosmetic appearance of the genitalia after reconstruction are reviewed. Material and methods Fifteen patients operated on between 2005 and 2015 were evaluated. Age at surgical repair ranged from 3 to 20 months (mean 9). Treatment included unfolding the preputial sac via a ventral approach, excision of redundant inner preputial skin, and ventral skin coverage with the outer preputial layer. Twelve patients presented associated partial scrotal engulfment, which was simultaneously treated. Mean follow-up was 4.6 years (range 2–7 years). Results Short-term complications occurred in three patients: scrotal hematoma in one patient and small skin dehiscence at the penoscrotal junction in two patients. Skin disruption healed by secondary epithelial ingrowth. All cases resulted in a satisfactory genital cosmetic outcome. There were no late complications. All patients preserved normal external genitalia appearance. Conclusion Our experience is in agreement with reports of other authors; suggesting that excision of the inner preputial layer and using the external one for penile coverage provide good and durable mid-term esthetic results in megaprepuce reconstruction.